Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

Local and Regional, Not Latitudinal, Variation in Microclimate and Bedrock Shapes Moss‐Associated Diatom Communities in Greenland - Charlotte Goeyers; Bart Van de Vijver; Tyler J. Kohler; Elie Verleyen; Bjorn Tytgat; S. Robbert Gradstein; Koen Sabbe (Journal of Biogeography, 2025)
Aim Greenland is among the most rapidly changing regions on Earth, with climate change having a profound impact on its terrestrial ecosystems. Here, moss‐associated diatoms hold great potential as sensitive biological indicators to monitor responses to climate change, but their diversity, community structure and biogeography remain virtually unexplored. Our study, thus, aims to (1) explore the diversity and community structure of moss‐associated diatoms in Greenland and (2) assess the environmental and spatial variables driving their geographic distribution, establishing a baseline for their use as bio‐indicators of climate change. Location Greenland, spanning a gradient from high to subarctic regions. Taxon Moss‐associated diatoms (Bacillariophyta). Methods LM and SEM analysis was conducted on 175 terrestrial moss samples collected from preserved herbarium material and fresh samples (1988–2021) from high, low and subarctic localities in Greenland. Biogeographical distributions, biodiversity patterns and community structure were examined in relation to environmental and spatial factors using Kruskal–Wallis, Spearman's Rank, ordination, SIMPROF and variation partitioning analyses. Results A total of 544 diatom taxa (66 genera) were identified, with nearly half potentially new to science. Community structure was predominantly influenced by moisture, pH, conductivity and temperature. Local variation in microclimate and bedrock, thus, explained more variation in the diatom communities than latitude‐related environmental gradients. Surprisingly, temperature had a negative impact on diatom richness, probably due to its adverse effect on moisture, highlighting the vulnerability of Arctic moss diatoms to global warming. Main Conclusions This study provides the first comprehensive analysis of Greenland's moss‐associated diatoms, highlighting their high diversity and sensitivity to environmental changes. Our findings underscore their potential as indicators for monitoring climate change in the Arctic, with moisture, pH, conductivity and temperature being critical factors influencing their communities, laying the groundwork for future research and monitoring efforts.

Geographical range in liverworts: does sex really matter? - Benjamin Laenen; Antonin Machac; S. Robbert Gradstein; Blanka Shaw; Jairo Patiño; Aurélie Désamoré; Bernard Goffinet; Cymon J. Cox; Jonathan Shaw; Alain Vanderpoorten (Journal of Biogeography, 2016)
Aim Why some species exhibit larger geographical ranges than others remains a fundamental, but largely unanswered, question in ecology and biogeography. In plants, a relationship between range size and mating system was proposed over a century ago and subsequently formalized in Baker's Law. Here, we take advantage of the extensive variation in sexual systems of liverworts to test the hypothesis that dioecious species compensate for limited fertilization by producing vegetative propagules more commonly than monoecious species. As spores are assumed to contribute to random long‐distance dispersal, whereas vegetative propagules contribute to colony maintenance and frequent short‐distance dispersal, we further test the hypothesis that monoecious species exhibit larger geographical ranges than dioecious ones. Location Worldwide. Methods We used comparative phylogenetic methods to assess the correlation between range size and life history traits related to dispersal, including mating systems, spore size and production of specialized vegetative propagules. Results No significant correlation was found between dioecy and production of vegetative propagules. However, production of vegetative propagules is correlated with the size of geographical ranges across the liverwort tree of life, whereas sexuality and spores size are not. Moreover, variation in sexual systems did not have an influence on the correlation between geographical range and production of asexual propagules. Main conclusions Our results challenge the long‐held notion that spores, and not vegetative propagules, are involved in long‐distance dispersal. Asexual reproduction seems to play a major role in shaping the global distribution patterns of liverworts, so that monoecious species do not tend to display, on average, broader distribution ranges than dioecious ones. Our results call for further investigation on the spatial genetic structure of bryophyte populations at different geographical scales depending on their mating systems to assess the dispersal capacities of spores and asexual propagules and determine their contribution in shaping species distribution ranges.

A comparison of alpha and beta diversity patterns of ferns, bryophytes and macrolichens in tropical montane forests of southern Ecuador - Nicole Mandl; Marcus Lehnert; Michael Kessler; S. Robbert Gradstein (Biodiversity and Conservation, 2010)

Vertical distribution of epiphytic bryophytes in an Indonesian rainforest - S. Goda Sporn; Merijn M. Bos; Michael Kessler; S. Robbert Gradstein (Biodiversity and Conservation, 2010)

Niche assembly of epiphytic bryophyte communities in the Guianas: a regional approach - Sylvia Mota de Oliveira; Hans Ter Steege; Johannes H. C. Cornelissen; S. Robbert Gradstein (Journal of Biogeography, 2009)
Aim Epiphytic bryophyte communities of tropical forests show a gradient in species composition from the base to the top of the host trees, indicating a strong role of niche assembly. This pattern, however, has never been tested at a regional scale. The aim of this study was to test whether niche assembly, rather than dispersal limitation, predominantly drives species composition of bryophyte communities across large spatial scales. Location Three lowland forests in the Guianas: one near Saul, French Guiana; and two near Mabura Hill, Guyana. Methods Communities of epiphytic bryophytes were sampled from six different height zones of several trees in three lowland forests. We analysed the composition of these communities using detrended correspondence analysis in order to find the best explanatory variable for the variation in community composition. A multi‐response permutation procedure was used to test the significance of grouping communities by height zone. We conducted an indicator species analysis to classify species as specialists or generalists and then tested, through weighted averaging, if specialists would indeed maintain their preferred height zone across the Guianas. Results Community composition was explained mainly by height zone. The similarity among communities inhabiting the same height zone of trees, across a distance of up to 640 km, was higher than the similarity among communities established along the vertical gradient of a single standing tree (30–50 m). More than half (57%) of the species had a preferred height zone, and the preference was consistent: species occupied roughly the same height zone on host trees in the different localities. The three local communities investigated were found to belong to the same regional species pool. Main conclusions Throughout the Guianas, epiphytic bryophyte communities are drawn from the same regional species pool, and their composition is shaped by micro‐environmental conditions. The predominance of niche assembly over dispersal assembly rules is consistently found at both local and regional scales.

Seedling establishment of vascular epiphytes on isolated and enclosed forest trees in an Andean landscape, Ecuador - Florian A. Werner; S. Robbert Gradstein (Biodiversity and Conservation, 2008)

Vertical stratification of vascular epiphytes in submontane and montane forest of the Bolivian Andes: the importance of the understory - Thorsten Krömer; Michael Kessler; S. Robbert Gradstein (Plant Ecology, 2007)

Diversity patterns of vascular epiphytes along an elevational gradient in the Andes - Thorsten Krömer; Michael Kessler; S. Robbert Gradstein; Amparo Acebey (Journal of Biogeography, 2005)
Aim To document the elevational pattern of epiphyte species richness at the local scale in the tropical Andes with a consistent methodology. Location The northern Bolivian Andes at 350–4000 m above sea level. Methods We surveyed epiphytic vascular plant assemblages in humid forests in (a) single trees located in (b) 90 subplots of 400 m 2 each located in (c) 14 plots of 1 ha each. The plots were separated by 100–800 m along the elevational gradient. Results We recorded about 800 epiphyte species in total, with up to 83 species found on a single tree. Species richness peaked at c. 1500 m and declined by c . 65% to 350 m and by c. 99% to 4000 m, while forests on mountain ridges had richness values lowered by c. 30% relative to slope forests at the same elevations. The hump‐shaped richness pattern differed from a null‐model of random species distribution within a bounded domain (the mid‐domain effect) as well as from the pattern of mean annual precipitation by a shift of the diversity peak to lower elevations and by a more pronounced decline of species richness at higher elevations. With the exception of Araceae, which declined almost monotonically, all epiphyte taxa showed hump‐shaped curves, albeit with slightly differing shapes. Orchids and pteridophytes were the most species‐rich epiphytic taxa, but their relative contributions shifted with elevation from a predominance of orchids at low elevations to purely fern‐dominated epiphyte assemblages at 4000 m. Within the pteridophytes, the polygrammoid clade was conspicuously overrepresented in dry or cold environments. Orchids, various small groups (Cyclanthaceae, Ericaceae, Melastomataceae, etc.), and Bromeliaceae (below 1000 m) were mostly restricted to the forest canopy, while Araceae and Pteridophyta were well represented in the forest understorey. Main conclusions Our study confirms the hump‐shaped elevational pattern of vascular epiphyte richness, but the causes of this are still poorly understood. We hypothesize that the decline of richness at high elevations is a result of low temperatures, but the mechanism involved is unknown. The taxon‐specific patterns suggest that some taxa have a phylogenetically determined propensity for survival under extreme conditions (low temperatures, low humidity, and low light levels in the forest interior). The three spatial sampling scales show some different patterns, highlighting the influence of the sampling methodology.

Phytogeography of the bryophyte floras of oak forests and páramo of the Cordillera de Talamanca, Costa Rica - Ingo Holz; S. Robbert Gradstein (Journal of Biogeography, 2005)
Aim Central America is a biogeographically interesting area because of its location between the rich and very different biota of North and South America. We aim to assess phytogeographical patterns in the bryophyte floras of oak forests and páramo of the Cordillera de Talamanca, Costa Rica. Location Tropical America, in particular the montane area of Cordillera de Talamanca, Costa Rica. Methods The analysis is based on a new critical inventory of the montane bryophyte flora of Cordillera de Talamanca. All species were assigned to phytogeographical elements on the basis of their currently known distribution. Absolute and percentage similarities were employed to evaluate floristic affinities. Results A total of 401 species [191 hepatics (liverworts), one hornwort, 209 mosses] are recorded; of these, 251 species (128 hepatics, one hornwort, 122 mosses) occur in oak forests. Ninety‐three per cent of all oak forest species are tropical in distribution, the remaining 7% are temperate (4%) and cosmopolitan (3%) species. The neotropical element includes almost 74% of the species, the wide tropical element (pantropical, amphi‐atlantic, amphi‐pacific) only 19%. A significant part of the neotropical species from oak forests are species with tropical Andean‐centred ranges (27%). As compared with bryophyte species, vascular plant genera in the study region are represented by fewer neotropical, more temperate and more amphi‐pacific taxa. Bryophyte floras of different microhabitats within the oak forest and epiphytic bryophyte floras on Quercus copeyensis in primary, early secondary and late secondary oak forest show a similar phytogeographical make‐up to the total oak forest bryophyte flora. Comparison of oak forest and páramo reveals a greater affinity of the páramo bryophyte flora to temperate regions and the great importance of the páramo element in páramo. Surprisingly, oak forests have more Central American endemics than páramo. Main conclusions (1) Providing first insights into the phytogeographical patterns of the bryophyte flora of oak forests and páramo, we are able to confirm general phytogeographical trends recorded from vascular plant genera of the study area although the latter were more rich in temperate taxa. (2) Andean‐centred species are a conspicuous element in the bryophyte flora of Cordillera de Talamanca, reflecting the close historical connection between the montane bryophyte floras of Costa Rica and South America. (3) High percentages of Central American endemics in the bryophyte flora of the oak forests suggest the importance of climatic changes associated with Pleistocene glaciations for allopatric speciation.

Cryptogamic epiphytes in primary and recovering upper montane oak forests of Costa Rica – species richness, community composition and ecology - Ingo Holz; Robbert S. Gradstein (Plant Ecology, 2005)

Impact of management intensity on non-vascular epiphyte diversity in cacao plantations in western Ecuador - Meike S. Andersson; S. Robbert Gradstein (Biodiversity and Conservation, 2005)

Tree diversity in primary forest and different land use systems in Central Sulawesi, Indonesia - Michael Kessler; Paul J.A. Keßler; S. Robbert Gradstein; Kerstin Bach; Michaela Schmull; Ramadhanil Pitopang (Biodiversity and Conservation, 2005)

Species diversity and endemism of five major Malesian islands: diversity–area relationships - Marco C. Roos; Paul J. A. Keßler; S. Robbert Gradstein; Pieter Baas (Journal of Biogeography, 2004)
Aim A comparison of biodiversity patterns within Malesia in relation to surface area. Location Analysis of the patterns in species richness and endemism of vascular plants in the five major Malesian islands, i.e. Java, Sulawesi, Sumatra, Borneo and New Guinea. Methods Available data on species richness and species ranges in correlation with the surface area of the respective islands were examined in this work. Estimations of total species numbers for these islands are presented based on extrapolation of all available published Flora Malesiana information and recent checklists, all in all comprising 12,000 different species. The regression analysis of overall species richness and endemism were studied for all species together as well as for different plant families to compare the fit with the Arrhenius species–area model. Results The five islands form a series of independent areas of increasing size suited for an analysis of the species–area relationships at the regional scale. All species taken together and those of families with even distribution throughout Malesia show significant species–area relationships. Non‐significant relationships were detected in families with western or eastern‐centred Malesian distribution patterns. Relationships between number of endemic species and surface area are significant for all species and for the majority of the families with significant species–area relationships. Main conclusions Species–area relationships of families appear to be dependent on species number. Families with high numbers of species usually have a significant species–area relationship whereas small families have not. For the families that display an eastern or western Malesian centred pattern, a historical biogeographical explanation should be invoked. Island surface area appears to be a predictor for island percent endemism in Malesian vascular plants. None of the islands appears to be a hotspot of endemism nor of species diversity, as no significant departure from the Arrhenius model was noted for any of them.